Translating textiles to tissue engineering: Creation and evaluation of microporous, biocompatible, degradable scaffolds using industry relevant manufacturing approaches and human adipose derived stem cells. Issue 5 (17th September 2014) - Haslauer, Carla M.; Avery, Matthew R.; Pourdeyhimi, Behnam; Loboa, Elizabeth G.
Abstract Polymeric scaffolds have emerged as a means of generating three‐dimensional tissues, such as for the treatment of bone injuries and nonunions. In this study, a fibrous scaffold was designed using the biocompatible, degradable polymer poly‐lactic acid in combination with a water dispersible sacrificial polymer, EastONE. Fibers were generated via industry relevant, facile scale‐up melt‐spinning techniques with an islands‐in‐the‐sea geometry. Following removal of EastONE, a highly porous fiber remained possessing 12 longitudinal channels and pores throughout all internal and external fiber walls. Weight loss and surface area characterization confirmed the generation of highly porous fibers as observed via focused ion beam/scanning electron microscopy. Porous fibers were then knit into a three‐dimensional scaffold and seeded with human adipose‐derived stem cells (hASC). Confocal microscopy images confirmed hASC attachment to the fiber walls and proliferation throughout the knit structure. Quantification of cell‐mediated calcium accretion following culture in osteogenic differentiation medium confirmed hASC differentiation throughout the porous constructs. These results suggest incorporation of a sacrificial polymer within islands‐in‐the‐sea fibers generates a highly porous scaffold capable of supporting stem cell viability and differentiation with the potential to generate large three‐dimensional constructs for bone regeneration and/or other tissue engineering applications. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 103B: 1050–1058, 2015.